ANALISIS SEGMENTASI USIA DONATUR TERHADAP PEMINATAN DONASI DI HUMAN INITATIVE - Wawan Eka Kurniawan; Sundjoto; Sri Rahayu (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to analyze to determine the age segmentation of donors on demand for donations in the Human Initiative. Where are legal institutions that form a community to collect donations, which can be accessed through social media and make it easier for the community to channel aid. The Human Initiative moves to help in the form of social activities, and distributes assistance to underprivileged communities, or communities affected by natural disasters in Indonesia. This study uses a descriptive quantitative research method which makes it easier for readers to find out the actual donor data, and is processed using an average calculation to find out the final result. with a sample collection technique taken from some of the donor data in 2019-2020 and 2021-2022, of course the population in the Human Initiative. In the calculation results in 2019-2020 age segmentation from 20-60 years, the results show that the average age of donors is 32, and the calculation of age segmentation in 2021-2022 with ages from 20-50 years, resulting from an average age of 32 years . Thus, it can be said that at 4 years, the age segmentation of Donors is in the interest of Donation with an average age of 32 years.